Education of IT professionals and emerging new technologies : are capable of keeping pace with technology and educate quality content builders at the same time? - Vrana, Radovan (Array, 2000)
Keeping pace with technology is the most challenging task in the world of IT professionals. This task is even more demanding for educators since they should be permanently aware of emerging technologies and ready to almost immediately pass their newly acquired knowledge to future IT professionals. With this thoughts in mind and looking at the available academic programs one can conclude that it is not always easy to choose between dedication to the technical side of implementation of new technologies (such as passing the knowledge about the building of new information resource infrastructure) and content creation. In the world of existing electronic online resources this problem is even more prominent. The most recent case in point is electronic resource which became widely known in last decade by the name of digital libraries (DL). At the initial stage of their development IT professionals around the world realized very quickly full complexity of building such a new information resource dedicating their time to solving different kinds of problems related mostly to the infrastructure and other technical issues rather then to content creation. After the completion of this initial technically oriented stage, problems concerning the copyright and quality content creation arose. In the year 2000, these two issues (among other things) still remain the most prominent and are still calling for solutions. In Croatia we still do not have a single digital library. However, electronic resources are used every day, most of them designed for scientific work (online databases) and bought as commercial products and the rest of them are resources of educational material prepared for students by the academic staff. Another thing we still do not have or at least not in adequate number are IT professionals specialized in original content creation, content selection and content presentation. Problem is even more acute if we think about overwhelming quantity of information available on the Internet which are in most cases free but of questionable quality and small number of quality resources accessible only to rather small number of people who can afford paying licenses to commercial databases. In such a situation we should invest more in education of IT professionals who would create original online content of high quality not only for scientists and students but also for everyone with access to the Internet here in Croatia.